SURVEY OF MANAGEMENT INFORMATION SYSTEMS AND THEIR LANGUAGES - Fry, James P.; Gosden, John A. (1968)
Significant data management systems available on third-generation hardware are considered. Three types of user interface are discussed: Own DML (Data Management Language) Systems, Forms Controlled Systems and POL Embedded Systems. Typical systems within each category are presented and their salient features are highlighted. See also Data management series no. 2, AD684707.